The sindacatus of the potestas during the 1300s: Giuliano Spinola’s, Reggio Emilia’s potestas, case study (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
This article intends to propose a brief examination of the institute of the sindicatus, especially in relation to the lordship and with particular attention to the peculiar case of Giuliano Spinola, potestas of the Commune of Reggio from 1372 to 1374. The register of convictions of the rector civitatis, dated 1374 and and kept at the State Archives of Reggio Emilia, is to be considered an exceptional source from different points of view. First, the documentary evidence relating to this type of process is rare: generally, these files were not kept for a long period of time. It is therefore unusual that the State Archives of Reggio Emilia have preserved the memory. Secondly, the register allows to reconstruct the judicial stages through which the final judgment was reached. Finally, it is possible to evaluate what was the intervention of the Visconti lordship in the communal government practices, as well as what were the relationships that existed between lordship power, urban magistratures and major officiality.
Keywords: Sindicatus; potestas; 13th century; Reggio Emilia; Visconti lordship